Ceramic slurry for improving wavy edge of diaphragm
By using improved ceramic slurry on the lithium-ion battery separator, including a specific proportion of alumina and wetting agent, the problem of large wavy edge ratio and low yield is solved, and the surface quality and yield of the separator is significantly improved.
Patent Information
- Application Number
- CN202411843840.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-14
- Publication Date
- 2025-03-07
AI Technical Summary
After the existing lithium-ion battery separators are coated with ceramics, the wavy side ratio is large and the yield is low, making it difficult to meet the battery safety performance and performance requirements.
A ceramic slurry that improves the wavy edge of the diaphragm is used, including alumina, water, adhesive, dispersant, organic solvent, thickener and wetting agent. The wetting agent uses a combination of alkyl polysaccharides and cocoa dihydroxyethyl amine oxide to adjust the slurry ratio and production process parameters to form tiny protrusions to reduce the wavy edges.
By adjusting the ratio of ceramic slurry and the production process parameters, the wavy side ratio of the coated diaphragm is significantly reduced, the yield is improved, and the serious problem of wavy side conditions is solved.
Smart Images

Figure CN119581790A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of battery separators, and in particular to a ceramic slurry for improving the wave edge of a separator. Background Art
[0002] The diaphragm is one of the four main components of lithium-ion batteries. It plays the role of isolating the positive and negative electrodes, preventing the positive and negative electrodes from short-circuiting, and providing channels for lithium ions to pass through. At present, in order to better match the safety and performance requirements of power batteries, the use of coated diaphragms in power batteries has gradually become the mainstream. By coating a ceramic coating on the base film, the thermal stability of the diaphragm can be greatly improved, the high-temperature shrinkage rate can be reduced, the exposure of the pole pieces caused by the large shrinkage of the diaphragm can be avoided, and the short circuit of the lithium-ion battery can be prevented, thereby improving the safety performance of the battery. However, compared with other material production systems, the diaphragm production process is complicated, especially the hardness increases after coating with ceramics. When the pressure mode is used for winding, the diaphragm has serious wavy edges, the proportion of wavy edges of the diaphragm is large, and the yield is low. Therefore, there is an urgent need for a coating slurry that can improve the wavy edges. Summary of the invention
[0003] The present invention proposes a ceramic slurry for improving the wave edge of a diaphragm, which solves the problem of a large wave edge ratio and low yield of a coated diaphragm in the related art.
[0004] The technical solution of the present invention is as follows: The present invention provides a ceramic slurry for improving the wave edge of a diaphragm, comprising the following components in parts by weight: 30-40 parts of aluminum oxide, 45-55 parts of water, 3-4 parts of an adhesive, 0.3-0.5 parts of a dispersant, 3.5-4.5 parts of an organic solvent, 6-8 parts of a thickener, and 0.01-0.15 parts of a wetting agent; The wetting agent comprises alkyl polyglycoside and coconut dihydroxyethyl amine oxide in a mass ratio of 1:9 to 9:1.
[0005] As a further technical solution, the wetting agent includes alkyl polyglycoside and coconut dihydroxyethyl amine oxide in a mass ratio of 4:1-6.
[0006] In the present invention, the wetting agent of the ceramic slurry is compounded with alkyl polyglycoside and coconut dihydroxyethyl amine oxide in a mass ratio of 4:1-6, which further reduces the wave edge ratio of the coating diaphragm and improves the yield.
[0007] As a further technical solution, the particle size D50 of the aluminum oxide is 0.7-0.9 μm.
[0008] As a further technical solution, the aluminum oxide is 2,2′-methylenedianiline modified aluminum oxide.
[0009] As a further technical solution, the preparation method of 2,2′-methylenedianiline modified alumina comprises the following steps: Dissolving 2,2′-methylenedianiline, mixing with alumina, and drying to obtain 2,2′-methylenedianiline modified alumina; The mass ratio of the 2,2′-methylenedianiline to the aluminum oxide is 1:15-18.
[0010] In the present invention, 2,2′-methylenedianiline is used to modify the aluminum oxide, thereby improving the agglomeration of the aluminum oxide, further reducing the wave edge ratio of the coating diaphragm, and improving the yield.
[0011] As a further technical solution, the thickener includes one or more of carboxymethyl cellulose, methyl cellulose, ethyl cellulose, and hydroxyethyl cellulose; The adhesive includes one or more of polymethyl methacrylate, acrylic resin, methacrylic acid, and acrylate; The organic solvent includes one or more of isopropanol, methanol and ethanol.
[0012] The present invention also proposes a method for preparing a ceramic slurry for improving the wavy edge of a diaphragm, comprising the following steps: The dispersant and water are mixed for the first time, alumina is added for the second mixing, and the remaining components are added for the third mixing to obtain a ceramic slurry.
[0013] As a further technical solution, the first mixing time is 5 to 10 minutes, the rotation speed is 1000 to 2500 r / min, and the revolution speed is 30 to 50 r / min; The second mixing time is 20-40 min, the rotation speed is 1000-2500 r / min, and the revolution speed is 30-50 r / min; The third mixing has a rotation speed of 1000-2500 r / min and a revolution speed of 30-50 r / min.
[0014] The present invention also provides a method for preparing a diaphragm, comprising the following steps: The ceramic slurry or the ceramic slurry obtained by the preparation method is coated on one side or both sides of the surface of the base film, and then dried to obtain a coating film.
[0015] As a further technical solution, the coating speed is 50-100 m / min; the coating thickness is 2-4 μm; the drying temperature is 60-80° C., and the drying time is 5-8 min.
[0016] The working principle and beneficial effects of the present invention are: In the present invention, by adjusting the ratio of the ceramic slurry and the parameters of the manufacturing process, the slurry forms tiny protrusions on the surface of the diaphragm, so that during the slitting and winding process of the diaphragm, a gap layer is formed between the diaphragms, leaving space for stress release, thereby reducing the wavy edge caused by stress release; Compared with the existing slurry, under the same winding pressure, the ratio of the wave edge before and after adjustment can be reduced by about 6%; at the same time, the problem of low yield when using the pressure mode for slitting with a width of more than 250mm is solved; At the same time, the ceramic slurry wetting agent is compounded with alkyl polysaccharide and coconut dihydroxyethyl amine oxide in a mass ratio of 1:9~9:1 to improve the leveling properties of the slurry, thereby improving the surface quality of the ceramic slurry after film formation on the surface of the diaphragm, significantly reducing the proportion of wavy edges of the coated diaphragm and improving the yield. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments.
[0018] Figure 1 This is a coating SEM image of the coating diaphragm prepared in Example 1 of the present invention; Figure 2 This is a SEM image of the coating of the coated diaphragm prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0019] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0020] In the following examples and comparative examples, the dispersant is sodium polyacrylate, the particle size D50 of aluminum oxide is 0.7-0.9 μm, the model of alkyl polyglycoside is APG-0810, and the molecular weight of PMMA is 100,000.
[0021] Example 1 A ceramic slurry for improving the wave edge of a diaphragm includes the following components in parts by weight: 35 parts of aluminum oxide, 50 parts of water, 4 parts of PMMA, 0.4 parts of a dispersant, 4 parts of isopropyl alcohol, 7 parts of a hydroxymethyl cellulose solution (solid content 5%), and 0.1 parts of a wetting agent; the wetting agent includes an alkyl polyglycoside and coconut oil dihydroxyethyl amine oxide in a mass ratio of 5:1; S1. First, the dispersant and water are stirred and blended in a planetary stirring device for 5 minutes (the rotation speed is 1000r / min and the revolution speed is 40r / min), and then the alumina is poured into a planetary stirring tank and blended for 30 minutes (the rotation speed is 2000r / min and the revolution speed is 40r / min). The remaining components of the ceramic slurry are added and mixed in a planetary stirring device at a rotation speed of 2000r / min and a revolution speed of 40r / min to obtain a ceramic slurry; S2, coating: placing the PE film on a coating machine equipped with the ceramic slurry obtained in step S1 for single-sided or double-sided coating, controlling the coating speed to 80 m / min, controlling the coating thickness to 2 μm, pulling the film into a drying device through a traction roller and drying it at 80° C. for 5 min to obtain a coated diaphragm. The surface coating SEM image of the coated diaphragm is as follows: Figure 1 shown.
[0022] Example 2 The ceramic slurry for improving the wave edge of the diaphragm includes the following components in parts by weight: 35 parts of aluminum oxide, 50 parts of water, 4 parts of PMMA, 0.4 parts of dispersant, 4 parts of isopropyl alcohol, 7 parts of hydroxymethyl cellulose solution (solid content 5%), and 0.1 parts of wetting agent; the wetting agent includes alkyl polysaccharide and coconut oil dihydroxyethyl amine oxide in a mass ratio of 1:9; S1. First, the dispersant and water are stirred and blended in a planetary stirring device for 5 minutes (the rotation speed is 1000r / min and the revolution speed is 40r / min), and then the alumina is poured into a planetary stirring tank and blended for 30 minutes (the rotation speed is 2000r / min and the revolution speed is 40r / min). The remaining components of the ceramic slurry are added and mixed in a planetary stirring device at a rotation speed of 2000r / min and a revolution speed of 40r / min to obtain a ceramic slurry; S2. Coating: Place the PE film on a coating machine filled with the ceramic slurry obtained in step S1 for single-sided or double-sided coating, control the coating speed to 80 m / min, control the coating thickness after coating to 3 μm, and pull it into a drying device through a traction roller and dry it at 80° C. for 5 minutes to obtain a coated diaphragm.
[0023] Example 3 The ceramic slurry for improving the wave edge of the diaphragm includes the following components in parts by weight: 35 parts of aluminum oxide, 50 parts of water, 4 parts of PMMA, 0.4 parts of dispersant, 4 parts of isopropyl alcohol, 7 parts of hydroxymethyl cellulose solution (solid content 5%), and 0.1 parts of wetting agent; the wetting agent includes alkyl polyglycoside and coconut oil dihydroxyethyl amine oxide in a mass ratio of 9:1; S1. First, the dispersant and water are stirred and blended in a planetary stirring device for 5 minutes (the rotation speed is 1000r / min and the revolution speed is 40r / min), and then the alumina is poured into a planetary stirring tank and blended for 30 minutes (the rotation speed is 2000r / min and the revolution speed is 40r / min). The remaining components of the ceramic slurry are added and mixed in a planetary stirring device at a rotation speed of 2000r / min and a revolution speed of 40r / min to obtain a ceramic slurry; S2. Coating: Place the PE film on a coating machine filled with the ceramic slurry obtained in step S1 for single-sided or double-sided coating, control the coating speed to 80 m / min, control the coating thickness after coating to 3 μm, and pull it into a drying device through a traction roller and dry it at 80° C. for 5 minutes to obtain a coated diaphragm.
[0024] Example 4 The ceramic slurry for improving the wave edge of the diaphragm includes the following components in parts by weight: 30 parts of aluminum oxide, 45 parts of water, 3 parts of PMMA, 0.3 parts of dispersant, 3.5 parts of isopropyl alcohol, 6 parts of hydroxymethyl cellulose solution (solid content 5%), and 0.01 parts of wetting agent; the wetting agent includes alkyl polysaccharide and coconut oil dihydroxyethyl amine oxide in a mass ratio of 5:1; S1. First, the dispersant and water are stirred and blended in a planetary stirring device for 5 minutes (the rotation speed is 1000r / min and the revolution speed is 30r / min), and then the alumina is poured into the planetary stirring tank and continued to be blended for 20 minutes (the rotation speed is 1000r / min and the revolution speed is 30r / min). The remaining components of the ceramic slurry are added and mixed in a planetary stirring device at a rotation speed of 1000r / min and a revolution speed of 30r / min to obtain a ceramic slurry; S2. Coating: Place the PE film on a coating machine filled with the ceramic slurry obtained in step S1 for single-sided or double-sided coating, control the coating speed to 50 m / min, control the coating thickness after coating to 2 μm, and pull it into a drying device through a traction roller and dry it at 60° C. for 8 minutes to obtain a coated diaphragm.
[0025] Example 5 A ceramic slurry for improving the wave edge of a diaphragm comprises the following components in parts by weight: 40 parts of aluminum oxide, 55 parts of water, 4 parts of PMMA, 0.5 parts of a dispersant, 4.5 parts of isopropyl alcohol, 8 parts of a hydroxymethyl cellulose solution (solid content 5%), and 0.15 parts of a wetting agent; the wetting agent comprises an alkyl polyglycoside and coconut oil dihydroxyethyl amine oxide in a mass ratio of 5:1; S1. First, the dispersant and water are stirred and blended in a planetary stirring device for 10 minutes (the rotation speed is 2500r / min and the revolution speed is 50r / min), and then the alumina is poured into the planetary stirring tank and continued to be blended for 50 minutes (the rotation speed is 2500r / min and the revolution speed is 30r / min). The remaining components of the ceramic slurry are added and mixed in a planetary stirring device at a rotation speed of 2500r / min and a revolution speed of 50r / min to obtain a ceramic slurry; S2. Coating: Place the PE film on a coating machine containing the ceramic slurry obtained in step S1 for single-sided or double-sided coating, control the coating speed to 100 m / min, control the coating thickness after coating to 2 μm, and pull it into a drying device through a traction roller and dry it at 80° C. for 5 minutes to obtain a coated diaphragm.
[0026] Example 6 The only difference between this embodiment and embodiment 1 is that the wetting agent is alkyl polyglycoside and coconut dihydroxyethyl amine oxide in a mass ratio of 4:8.
[0027] Example 7 The only difference between this embodiment and embodiment 1 is that the wetting agent is alkyl polyglycoside and coconut dihydroxyethyl amine oxide in a mass ratio of 4:1.
[0028] Example 8 The only difference between this embodiment and embodiment 1 is that the wetting agent is alkyl polyglycoside and coconut dihydroxyethyl amine oxide in a mass ratio of 4:6.
[0029] Example 9 The difference between this example and Example 8 is that the aluminum oxide is replaced with 2,2′-methylenedianiline modified aluminum oxide; The preparation method of 2,2′-methylenedianiline modified alumina comprises the following steps: 1 g of 2,2′-methylenedianiline was dissolved in 50 mL of chloroform, and 15 g of alumina was added, mixed, and dried to obtain 2,2′-methylenedianiline modified alumina.
[0030] Example 10 The difference between this example and Example 8 is that the aluminum oxide is replaced with 2,2′-methylenedianiline modified aluminum oxide; The preparation method of 2,2′-methylenedianiline modified alumina comprises the following steps: 1 g of 2,2′-methylenedianiline was dissolved in 50 mL of chloroform, and 18 g of alumina was added, mixed, and dried to obtain 2,2′-methylenedianiline-modified alumina.
[0031] Comparative Example 1 The ceramic slurry for improving the wave edge of the diaphragm includes the following components in parts by weight: 35 parts of aluminum oxide, 50 parts of water, 4 parts of PMMA, 0.4 parts of dispersant, 4 parts of isopropyl alcohol, 7 parts of hydroxymethyl cellulose solution (solid content 5%), and 0.1 parts of wetting agent; the wetting agent is alkyl polyglycoside; S1. First, the dispersant and water are stirred and blended in a planetary stirring device for 5 minutes (the rotation speed is 1000r / min and the revolution speed is 40r / min), and then the alumina is poured into a planetary stirring tank and blended for 30 minutes (the rotation speed is 2200r / min and the revolution speed is 40r / min), and then sand milled (speed 1250r / min), and the remaining components of the ceramic slurry are added in a planetary stirring device and mixed at a rotation speed of 2200r / min and a revolution speed of 40r / min to obtain a ceramic slurry; S2, coating: placing the PE film on a coating machine equipped with the ceramic slurry obtained in step S1 for single-sided or double-sided coating, controlling the coating speed to 80 m / min, controlling the coating thickness to 2 μm, pulling the film into a drying device through a traction roller and drying it at 80° C. for 5 min to obtain a coated diaphragm; the surface coating SEM image of the coated diaphragm is as follows: Figure 2 shown.
[0032] Comparative Example 2 The only difference between this comparative example and Example 1 is that the wetting agent is an alkyl polyglycoside.
[0033] Comparative Example 3 The only difference between this comparative example and Example 1 is that the wetting agent is coconut dihydroxyethyl amine oxide.
[0034] The yield and droop ratio tests were performed on the coated diaphragms prepared in Examples 1 to 10 and Comparative Examples 1 to 3 respectively: Yield: Yield statistics use manual judgment of defects to input into the system, and then the system pulls the yield situation; Sagging ratio: visual inspection was adopted, and the 2m diaphragm was pulled apart horizontally to check the sagging situation. If the sagging height exceeded 3mm, it was judged as sagging. Finally, the number of sagging was counted and compared with the statistical number. The results are shown in Table 1 below.
[0035] Table 1 Test results of coated diaphragms
[0036] Compared with Comparative Examples 1 to 3, the coating diaphragms prepared in Examples 1 to 10 have a higher yield and a lower proportion of sagging, indicating that the wavy edge caused by stress release is reduced by adjusting the ratio of the ceramic slurry and the production process parameters. At the same time, the ceramic slurry wetting agent is compounded with alkyl polysaccharide and coconut dihydroxyethyl amine oxide in a mass ratio of 1:9 to 9:1, which significantly reduces the wavy edge ratio of the coating diaphragm and improves the yield.
[0037] Compared with Example 1 and Example 6, the coating diaphragms prepared in Examples 7 to 8 have a higher yield and a lower sagging ratio, indicating that the wetting agent of the ceramic slurry is compounded with alkyl polysaccharide and coconut dihydroxyethyl amine oxide in a mass ratio of 4:1 to 6, which further reduces the wavy edge ratio of the coating diaphragm and improves the yield.
[0038] Compared with Example 8, the coated diaphragms prepared in Examples 9 to 10 have a higher yield and a lower droop ratio, indicating that the use of 2,2′-methylenedianiline to modify alumina improves the agglomeration of alumina, further reduces the wavy edge ratio of the coated diaphragm, and improves the yield.
[0039] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A ceramic slurry for improving the wave edge of a diaphragm, characterized in that: The invention comprises the following components in parts by weight: 30-40 parts of aluminum oxide, 45-55 parts of water, 3-4 parts of adhesive, 0.3-0.5 parts of dispersant, 3.5-4.5 parts of organic solvent, 6-8 parts of thickener, and 0.01-0.15 parts of wetting agent; The wetting agent comprises alkyl polyglycoside and coconut dihydroxyethyl amine oxide in a mass ratio of 1:9 to 9:
1.
2. The ceramic slurry for improving the diaphragm wave edge according to claim 1, characterized in that: The wetting agent comprises alkyl polyglycoside and coconut dihydroxyethyl amine oxide in a mass ratio of 4:1-6.
3. The ceramic slurry for improving the diaphragm wave edge according to claim 1, characterized in that: The particle size D50 of the aluminum oxide is 0.7-0.9 μm.
4. The ceramic slurry for improving the diaphragm wave edge according to claim 1, characterized in that: The aluminum oxide is 2,2'-methylenedianiline modified aluminum oxide.
5. The ceramic slurry for improving the diaphragm wave edge according to claim 4, characterized in that: The preparation method of 2,2′-methylenedianiline modified aluminum oxide comprises the following steps: Dissolving 2,2′-methylenedianiline, mixing with alumina, and drying to obtain 2,2′-methylenedianiline modified alumina; The mass ratio of the 2,2′-methylenedianiline to the aluminum oxide is 1:15-18.
6. The ceramic slurry for improving the diaphragm wave edge according to claim 1, characterized in that: The thickener includes one or more of carboxymethyl cellulose, methyl cellulose, ethyl cellulose, and hydroxyethyl cellulose; The adhesive includes one or more of polymethyl methacrylate, acrylic resin, methacrylic acid, and acrylate; The organic solvent includes one or more of isopropanol, methanol and ethanol.
7. A method for preparing a ceramic slurry for improving the diaphragm wave edge according to any one of claims 1 to 6, characterized in that: The following steps are involved: The dispersant and water are mixed for the first time, alumina is added for the second mixing, and the remaining components are added for the third mixing to obtain a ceramic slurry.
8. The method for preparing a ceramic slurry for improving the diaphragm wave edge according to claim 7, characterized in that: The first mixing time is 5-10 min, the rotation speed is 1000-2500 r / min, and the revolution speed is 30-50 r / min; The second mixing time is 20-40 min, the rotation speed is 1000-2500 r / min, and the revolution speed is 30-50 r / min; The third mixing has a rotation speed of 1000-2500 r / min and a revolution speed of 30-50 r / min.
9. A method for preparing a diaphragm, characterized in that: The following steps are involved: The ceramic slurry described in any one of claims 1 to 6 or the ceramic slurry prepared by the preparation method described in any one of claims 7 to 8 is coated on one side or both sides of the surface of the base film, and then dried to obtain a coated diaphragm.
10. The method for preparing a diaphragm according to claim 9, characterized in that: The coating speed is 50-100 m / min; the coating thickness is 2-4 μm; the drying temperature is 60-80° C., and the drying time is 5-8 min.